OFR-57-73 Development Of Multiplexed Borehole Inclinometer Probe, Data Acquisition And Calculation System ? 1. Introduction (The National Institute for Occupational Safety and Health (NIOSH), 2012)
During the initial portion of the contract several alternative designs were considered, as set out step by step in the monthly reports. The conclusions reached during this period were - to use on INTERDATA Model 70 as the system minicomputer - to drop the idea of multiplexing and digitizing the inclinometer outputs downhole due to the greater complexity and cost that that alternative would imply - to use a multitasking software monitor to enable synchronization of the several tasks that the system would have to perform simultaneously - to use a common controller for all I/0 devices except those which were available off the shelf from Interdata - to use a sheave counter to meter off equal increments of probe travel, but to supplement this information with the use of an encoder on the winch drum in order to be able to measure total probe travel unambiguously. - to place all I10 device interfaces in a bin connected to the common controller. During this period considerable attention was dedicated to the design of the mechanical components contemplated it the original contract. Of these, only those required for vertical probe was complete at the time that it was decided to forego the mechanical subsystem and concentrate on developing the necessary electronics and software to interface with the probes being developed by the Bureau of Mines.